2020
DOI: 10.1371/journal.pone.0237495
|View full text |Cite
|
Sign up to set email alerts
|

Levels of and determinants for physical activity and physical inactivity in a group of healthy elderly people in Germany: Baseline results of the MOVING-study

Abstract: Background Low levels of physical activity (PA) and high levels of physical inactivity (PI) are associated with higher mortality and cardiovascular diseases. Higher age is associated with a decrease of PA, only 2.4–29% of ≥60 year-olds achieve the PA times recommended by WHO. The aim of this study was to identify levels of and determinants for moderate PA, overall PA and PI in a sample of individuals aged ≥65 years. Methods We analyzed baseline data from an intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
2
14
0
1
Order By: Relevance
“…As previous research has shown, interventions should focus on the target group and especially on individual factors (e.g. age, sex) [ 46 ]. In addition, an inclusion of environmental and interpersonal factors can be helpful to change participants’ behavior [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As previous research has shown, interventions should focus on the target group and especially on individual factors (e.g. age, sex) [ 46 ]. In addition, an inclusion of environmental and interpersonal factors can be helpful to change participants’ behavior [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…age, sex) [ 46 ]. In addition, an inclusion of environmental and interpersonal factors can be helpful to change participants’ behavior [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body mass index (BMI) next 1 month in the study cohort, which was statistically significantly associated with the control group (CG) (P < 0.0001) (SANDEEP et al 2016). The body mass index was a significant difference element for overall Physical activity both in males and females as well as for moderate physical activity (MPA) for women (KLEINKE et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…High education level has a positive effect on PA and educated people are more physically active and pay more attention to their health [ 26 , 27 ]. Varo and al (EU study) showed that people with primary level education were more sedentary than people with higher levels of education [ 28 ].…”
Section: Discussionmentioning
confidence: 99%